Occupational fall incidence associated with heated tobacco product use and lifestyle behaviors in Japan - Saki Tsushima; Kazuhiko Watanabe; Sora Hirohashi; Tomohiro Yoshimi; Yoshihisa Fujino; Takahiro Tabuchi; Masayoshi Zaitsu (Scientific Reports)
Abstract This study identifies the association between heated tobacco product (HTP) use and occupational falls, considering lifestyle variables. A nationwide web-based cross-sectional study between September and November 2023 analyzed data from 18,440 workers in Japan (mean age: 43 years; women: 43.9%). The primary outcome was the occupational falls in the past year. The secondary outcome was fall-related fractures. Participants were categorized as those who never used, those who formerly used, and those who currently used tobacco products; the lattermost were further classified according to the product used. Other behavioral factors included alcohol consumption, sleep duration, physical activity, comorbidities, body mass index, hypnotics/anxiolytic use, and sociodemographic variables. Overall, 7.3% participants reported occupational falls, and 2.8% reported fall-related fractures. Occupational fall incidence was higher for those who currently smoked (IR: 1.36, 95% CI: 1.20–1.54), particularly those who exclusively used HTPs (IR: 1.78) and those who used both conventional cigarettes and HTPs (IR: 1.64), than for those who never smoked. Fall-related fractures showed similar trends. Short sleep duration and diabetes were associated with increased fall risk, particularly among younger workers. These findings highlight the significant association between HTP use, lifestyle behaviors, and occupational falls.